Impact of PROGRESA on achievement test scores in the first year: final report - Behrman, Jere R.; Sengupta, Piyali; Todd, Petra E. (International Food Policy Research Institute, 2000)
Increasing human capital investments in children is considered to be among the most effective ways of alleviating poverty and encouraging growth in developing countries. One possibly important channel through which such investments may have such impacts is through increasing cognitive achievement of children. Previous literature suggests that improved cognitive achievement has payoffs in terms of greater wages and perhaps productivities in labor markets in developing countries. This paper evaluates the short-run effects on children’s cognitive achievements of PROGRESA. One major component of PROGRESA is transfer payments to poor families with children enrolled in grades 3-6 of primary school and grades 1-3 of secondary school. Other components of PROGRESA include general transfers to such families and explicit nutrition supplements and health support for infants and small children. PROGRESA might have impact on children’s cognitive achievement through a number of channels, some of which are relatively short run and others are relatively longer run. Previous IFRPI-PROGRESA Evaluation Project papers have considered some aspects of possible changes induced by PROGRESA that may have led or may eventually lead to improved cognitive achievement. But none of these studies consider the effects on child achievement test scores.